ANALISIS KEBIJAKAN EVALUASI DAN PEMBELAJARAN DAN INOVASI STRATEGIS DALAM MENINGKATKAN KUALITAS PENDIDIKAN DASAR - Weni Yulastri; Zilfa Yeni; Meri Yessari; Bismi Afia; Yolanda Rahmadani Putri; Devira Syafitri Amizi; Azizah Nurazila (STKIP Subang, 2025)
This article discusses the policy issues in elementary schools related to learning evaluation in the context of the simultaneous implementation of two curricula, namely the 2013 Curriculum and the Merdeka Curriculum. The main problems include the mismatch in implementation, suboptimal learning evaluation, and limitations in resources and infrastructure. The methods used in this article are literature review and field observation. The analysis results indicate that policy innovations such as strengthening formative assessments, curriculum flexibility, teacher training, and the use of technology are essential to enhance independent learning and overall educational quality. This article recommends evidence-based and participatory policy formulation strategies.